SCADA Monitoring Design Using Multiple Siemens PLCs Based on a LAN Network - Wahidah, Wahidah; Insan, Asyraful; Rasul, Muhammad (INTEK: Jurnal Penelitian, 2024)
In the DCS SCADA practicum in the PLC laboratory at ATI Makassar Polytechnic there were connection problems between the PLC and PC, these problems could vary, including damaged cables, loose connectors, or interference with the communication port on the PC or PLC. This research aims to design and create a SCADA monitoring system using multiple PLCs based on a LAN network. In this research, 3 display modules were created that detect connection problems on 3 PLCs. Each module focuses on 1 PLC with a different IP and when there is a problem with the PLC A, B, & C connection, the LED on the PLC_S7-1200 text will flash. Then testing was carried out on the PC and PLC network connections using the PING statistics command through estimated round trip times. Next, test the network connection via accessible devices flashed on the PLC, test the tag on Kepserverex, test the Factory I/O, and test the PLC communication with the Factory I/O. Based on the results of the system testing carried out, namely testing the network connection on the PC and PLC, the round trip times on PC 1, 2, 3 showed an average of 2.4 ms, and on PLC 1, 2, 3 the average was 2.4 ms. with testing times of 1, 2, 5, 10, 20 minutes. Testing network connections via flashled accessible devices functions by displaying a light indicator when the PLC is flashing, then testing tags on Kepserverex displays a table containing the tags used and shows good quality. Then the Factory I/O test displays the access name and tag used, then the HMI display module being tested runs according to the system that has been implemented, as well as testing the PLC communication with Factory I/O to connect the Factory I/O software with the PLC.